2013
DOI: 10.1371/journal.pone.0063759
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine-5'-Triphosphate (ATP) Protects Mice against Bacterial Infection by Activation of the NLRP3 Inflammasome

Abstract: It has been established that Adenosine-5'-triphosphate (ATP) can activate the NLRP3 inflammasome. However, the physiological effect of extracellular ATP on NLRP3 inflammasome activation has not yet been investigated. In the present study, we found that ATP was indeed released during bacterial infection. By using a murine peritonitis model, we also found that ATP promotes the fight against bacterial infection in mice. ATP induced the secretion of IL-1β and chemokines by murine bone marrow-derived macrophages in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 38 publications
2
38
0
Order By: Relevance
“…141,[177][178][179] Moreover, extracellular ATP promotes the activation of the NLR family, pyrin domain containing 3 (NLRP3) inflammasome in APCs, hence stimulating the processing and release of interleukin (IL)-1b and IL-18. 119,[180][181][182][183][184][185][186][187][188][189] In line with this notion, the immunogenic potential of cells succumbing to ICD can be significantly reduced by pharmacological or genetic interventions that limit the availability of ATP in the pericellular space, such as the administration of recombinant apyrase (an ATP-degrading enzyme) or the transfection-enforced overexpression of ectonucleoside triphosphate diphosphohydrolase 1 (ENTPD1, best known as CD39), which converts ATP into ADP and AMP. 190 Intriguingly, CD39 and 5 0 -nucleotidase, ecto (NT5E, best known as CD73), which transforms AMP into adenosine, are often overexpressed by malignant tissues.…”
Section: Immunogenic Cell Death Signalingmentioning
confidence: 94%
“…141,[177][178][179] Moreover, extracellular ATP promotes the activation of the NLR family, pyrin domain containing 3 (NLRP3) inflammasome in APCs, hence stimulating the processing and release of interleukin (IL)-1b and IL-18. 119,[180][181][182][183][184][185][186][187][188][189] In line with this notion, the immunogenic potential of cells succumbing to ICD can be significantly reduced by pharmacological or genetic interventions that limit the availability of ATP in the pericellular space, such as the administration of recombinant apyrase (an ATP-degrading enzyme) or the transfection-enforced overexpression of ectonucleoside triphosphate diphosphohydrolase 1 (ENTPD1, best known as CD39), which converts ATP into ADP and AMP. 190 Intriguingly, CD39 and 5 0 -nucleotidase, ecto (NT5E, best known as CD73), which transforms AMP into adenosine, are often overexpressed by malignant tissues.…”
Section: Immunogenic Cell Death Signalingmentioning
confidence: 94%
“…ATP activation of the NLRP3 inflammasome protects mice against bacterial infection [122]. The P2X7 receptor plays a role in acute and chronic stages of infection as well as a 'danger signal' in the initial stages of inflammation (see [71]).…”
Section: Pathology and Inflammationmentioning
confidence: 99%
“…Recently, the physiological effect of extracellular ATP on NLRP3 inflammasome activation was investigated in the context of bacterial infection (16). Why and how ATP is released during bacterial infection are still unknown.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms of ATP release are well characterized for vesicular cells and excitatory/ secretory tissues; however, the mechanisms of ATP release from immune cells, such as macrophages, have not been well characterized. Actually, a recent paper showed that ATP could be released from infected immune cells and immune responses upregulated through activating NLRP3 inflammasomes, but the correlation between ATP release and Toll-like receptor (TLR) signaling is still indistinct (16). Therefore, the exploration of the internal relationship between ATP release and TLR-mediated innate immune responses against bacterial infection is justified and worthwhile.…”
mentioning
confidence: 99%